Origins of lacrimal surgery, and evolution of dacryocystorhinostomy to the present. (4th August 2013) - Harish, Varun; Benger, Ross S
Abstract The creation of an alternative pathway from the lacrimal sac into the nose has been practised for over two millennia. Early historical figures who pioneered lacrimal surgery were Celsus and Galen, treating dacryocystitis by plunging a red‐hot cautery iron through the lacrimal bone into the nose. Better understanding of lacrimal physiology and anatomy led to the introduction of more sophisticated techniques in the 18th century. However, despite these approaches, the technique of Celsus continued to be practised well into the eighteenth and nineteenth centuries. Modern lacrimal surgery began when the Italian otolaryngologist, Toti, described his external dacryocystorhinostomy procedure in 1904. Dupuy‐Dutemps and Bourget refined Toti's procedure, and introduced the technique of anastomosing lacrimal and nasal mucosal flaps which remains the foundation of the external dacryocystorhinostomy performed today. The endonasal dacryocystorhinostomy was described before the external approach, but its popularity and success grew only in recent times.